SPECIAL-INTEREST MARINE TOURISM DEVELOPMENT IN SERANGAN VILLAGE, DENPASAR - I Ketut Suarta; Anak Agung Putu Swabawa; I Putu Budiarta (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2017)
This resarch is held in Serangan Village, Denpasar Selatan District, Denpasar Municipility. Purpose of this researchis to identify the potencies of Serangan Island which could be developed as tourism product such as special-interest marine tourism and to know the visitors’ perceptions to the objects and attractions they visit in order to determine the most favorite tourist attraction in Serangan Village.Data of this research was collected by survey, interview, documentation and library study. The data is analyzed by using quantitative analysis (descriptive statistics)and qualitative analysis (descriptive and comparative analysis). The resultsshowed that there are five potencies of natural attractions identified in Serangan Island which could be developed as tourist objects and special-interest marine tourism. They are the white sand beach, seaweed, clean blue sea, coral garden, and mangrove forest. The special interest-marine tourism are surfing, parasailing, waterski, snorkeling, diving, flying fish, underwater seawalker, banana boat, jetski, donat boat, glass bottom boat, horse riding, fishing, fast boat, turtle conservation and coral transplantation. The biggest market segment of those special marine attractions are 95 % Chinese. The foreign visitors that visit Serangan Island about 94.41 %, and the domestic visitors are about 5.59 %. The most favorite marine attractions in Serangan Village is travelling through the quay by fast boat, it is 311,344 people. Then the second and third favorite are turtle conservation and parasailing, they are 18,040 people and 1,890 people. From the capacity ratio, the most favorite attraction is travelling through the quay by fast boat, it is 276.75, the second and third favorites are flying fish and underwater sea walker with ratio 157.50 and 132.38.